1999
DOI: 10.1086/307734
|View full text |Cite
|
Sign up to set email alerts
|

WHAM Observations of Hα, [Sii], and [Nii] toward the Orion and Perseus Arms: Probing the Physical Conditions of the Warm Ionized Medium

Abstract: A large portion of the Galaxy (ℓ = 123 • to 164 • , b = −6 • to −35 • ), which samples regions of the Local (Orion) spiral arm and the more distant Perseus arm, has been mapped with the Wisconsin H-Alpha Mapper (WHAM) in the [S II] λ6716 and [N II] λ6583 lines. By comparing these data with the maps from the WHAM Hα Sky Survey, we begin an investigation of the global physical properties of the Warm Ionized Medium (WIM) in the Galaxy. Several trends noticed in emission-line investigations of diffuse gas in other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
268
2
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(293 citation statements)
references
References 34 publications
16
268
2
7
Order By: Relevance
“…The distance to the Perseus arm is about 2:5 AE 0:5 kpc (see Reynolds et al 1995 and references therein). Haffner et al (1999) studied the H emission from the high-z extension of the Perseus arm and find that it has a scale height of about 1 kpc. Associated gas at b ¼ À45 would be at a distance of 3:6 AE 0:7 kpc and lie 2:5 AE 0:5 kpc below the Galactic plane.…”
Section: Location In the Milky Waymentioning
confidence: 99%
“…The distance to the Perseus arm is about 2:5 AE 0:5 kpc (see Reynolds et al 1995 and references therein). Haffner et al (1999) studied the H emission from the high-z extension of the Perseus arm and find that it has a scale height of about 1 kpc. Associated gas at b ¼ À45 would be at a distance of 3:6 AE 0:7 kpc and lie 2:5 AE 0:5 kpc below the Galactic plane.…”
Section: Location In the Milky Waymentioning
confidence: 99%
“…Much information regarding the source(s) of ionization has come from optical emission line ratios in the Milky Way and external galaxies (e.g., Rand 1997Rand , 1998bGreenawalt et al 1997;Collins & Rand 2001;Otte et al 2002;Haffner et al 1999;Hoopes & Walterbos 2003;Madsen et al 2006). Studies of the spatial behavior of several diagnostic line ratios have supported the idea that photoionization by massive stars is the primary ionization mechanism, but crucial aspects of the data require a more complex picture.…”
Section: Emission Lines From Digmentioning
confidence: 99%
“…The most characteristic result is that the ratios of [S ii] kk6716, 6731 and [N ii] kk6548, 6583 to H generally increase with distance from the suspected ionizing source, in the Milky Way and in external galaxy disks and halos. This was initially interpreted as a fall in the ionization parameter, U, with distance from the ionizing source (e.g., Domgorgen & Mathis 1994;Rand 1998b) but more recently has been attributed to an increase in the gas temperature in the DIG relative to the immediate star-forming environment due to a source of extra nonionizing heating (e.g., Haffner et al 1999;Otte et al 2002, using further information from [O ii] k3727/H in edge-on galaxies), while even more recently the importance of radiation field hardening during propagation (due to the longer mean free path for harder photons) has been stressed (Hoopes & Walterbos 2003;Wood & Mathis 2004, hereafter WM04).…”
Section: Emission Lines From Digmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a large fraction of the Galaxy contains fully ionized gas of 8000 K with an electron density of approximately 0.2 cm −3 . Low ionization lines, such as [S ii] λ6716 and [N ii] λ6587, have been widely detected in the WIM and they have been used for the study of the properties of the WIM (e.g., Haffner et al 1999 and references therein), while a high ionization line of [O iii] λ5007 is quite weak and has been detected only at two positions in the Galactic disk (Reynolds 1985). Latest studies suggest the presence of external heat sources in the Galactic halo to explain the spatial distribution and strength of these emission lines (Reynolds 1997;Reynolds et al 1999).…”
Section: Eld H II Regionmentioning
confidence: 99%